Peningkatan Pengetahuan Penilaian Sikap Berbasis Profil Pelajar Pancasila di SMPN 1 Wonosalam - Diah Puji Nali Brata; Edy Setiyo Utomo; Esty Saraswati Nur Hartiningrum (STIE Malangkucecwara, 2022)
Profil Pelajar Pancasila is currently the basis for the development of education in Indonesia. The purpose of this service is to increase teacher knowledge in the preparation of instruments and indicators of attitude assessment based on the Pancasila Student Profile. This service method consists of three stages, namely preparation, implementation and evaluation. This service activity was carried out at SMPN 1 Wonosalam, attended by 30 teachers. The results of the service showed that the activities were carried out in 2 sessions, where each session contained different material. Evaluation of activities through a questionnaire of 10 items, where the average of each item is 84.7%. Furthermore, the value dimension of the Pancasila Student Profile that is often applied in the classroom is the Faith dimension, and on the other hand the dimension that is rarely applied in the classroom is Global Diversity. Therefore, this service activity can be said to be effective and good in increasing the knowledge of SMPN 1 Wonosalam teachers regarding the Pancasila Student Profile. It is hoped that schools will continue to develop teacher knowledge about the Pancasila Student Profile in the form of ongoing assistance so that teachers can apply them optimally